Ergebnisse der Sicca-Forschungsförderung 2016 - Musayeva, A; Gericke, A; Jäger, Franziska; Paulsen, Friedrich; Braun, M; Fabry, Ben; Braun, R; Pauly, Diana; Holtmann, C; Geerling, Gerd; Goldblum, David; Horwath-Winter, Jutta; et al. (Ophthalmologe, 2020)
The Sicca-Förderpreis (Dry Eye Award) supports the development of scientific research on the pathogenesis, diagnostics, and treatment of dry eye and ocular surface diseases. It is awarded after a limited call for proposals in German-speaking countries, written application and selection of the award winner after evaluation by a jury of ophthalmologists working in basic and clinical science. In this article examples of the results of funded projects of the Sicca-Förderpreis 2016 are cursorily described, which were presented at the Ophthalmological Academy of Germany 2019 (Augenärztliche Akademie Deutschland 2019) and therefore provide an insight into current scientific developments. The role of muscarinic receptors and those of urea in the pathogenesis of dry eye as well as the (missing) correlation of tear film stability, viscosity and surface tension are highlighted. A project on the early detection of ocular involvement in graft versus host disease and the idea of treating meibomian gland dysfunction with eyelid surgery techniques are also groundbreaking. The outlined projects represent the potential for further substantial developments in the understanding, diagnostics and treatment of dry eye; however, their long-term clinical relevance still needs to be established.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Eyelid tension; Graft versus host disease; Muscarinic receptor; Tear film stability; Urea

Immunohistochemical detection of urea transporter-A in the tear- producing part of the lacrimal system - Jäger, Franziska; Paulsen, Friedrich; Bergua, Antonio; Jungbauer, Rebecca; Hammer, Christian (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Objective: Urea constitutes a physiological and presumably well-regulated constituent of tear fluid. Its la-crimal concentration is significantly decreased in dry eye disease. Urea homeostasis within the tear fluid may also depend on the expression of urea transporters. The present study reports on the expression patterns of urea transporter A (UT-A) in the cells and tissues of the ocular surface and the lacrimal glands. Methods: UT-A immunohistochemistry was performed on 5 mu m paraffin sections of paraformaldehyde-fixed human, porcine, and murine corneas, eyelids, and lacrimal glands (n = 5 each). Results: UT-A immunostaining was largely comparable in all three species. UT-A signals were detected in the corneal epithelium and endothelium, in the conjunctival epithelium, in the acinar cells and excretory ducts of the lacrimal gland, Meibomian gland, and in the glands of Moll and Zeis. The Meibomian glands and the glands of Zeis exhibited a marked UT-A-positive staining in the basal cells of the alveolar epithelia and in the ductal epithelia. Conclusion: UT-A shows comparable expression patterns to UT-B (previous study) at the ocular surface and in the lacrimal glands, as determined by immunohistochemistry. The presence of both urea transporters in the lacrimal functional unit suggests that they are essential for the normal function of the lacrimal system and the integrity of the tear film. Potential alterations in urea transporter expression might be associated with the significant reduction of urea found in the tear fluid of dry eye patients. They may thus play an important role in the pathogenesis of dry eye disease. (c) 2022 Elsevier GmbH. All rights reserved.
CRIS-Team WoS Importer:2022-09-16

Urea transporter-B expression on the ocular surface and in the lacrimal glands - Jäger, Franziska; Paulsen, Friedrich; Bergua, Antonio; Jungbauer, Rebecca; Hammer, Christian (Annals of Anatomy-Anatomischer Anzeiger, 2022)
Objective: Urea is a component of tear fluid showing a significantly decreased concentration in dry eye disease. The urea content of tear fluid may depend on urea transporters. The purpose of this study was to examine the expression of urea transporter B (UT-B) at the ocular surface and in the lacrimal glands. Methods: UT-B protein and mRNA expression was investigated in human, porcine, and murine samples. Immunohistochemical staining for UT-B was performed on paraffin sections of human, porcine, and murine corneas, eyelids, and lacrimal glands (n = 5 each). Reverse transcriptase polymerase chain reaction was conducted to detect UT-B mRNA in human and murine cornea, conjunctiva, Meibomian gland, and lacrimal gland (n = 5 each). Results: UT-B protein expression was comparable in all three species. It was found in the corneal epithelium and endothelium, in the conjunctival epithelium, in the end pieces and excretory ducts of the lacrimal gland, Meibomian gland, and in the glands of Moll and Zeis. The glands of Zeis and the Meibomian glands showed intense UT-B signals in the basal layers of the alveolar epithelia and in the cells of the ductal epithelia. UT-B mRNA was detected in all samples analyzed. Conclusion: UT-B is expressed by the cells and tissues of the ocular surface and in the lacrimal glands. Potential changes in urea transporter expression might have implications for the pathogenesis of dry eye disease. Since comparable results were obtained for all species investigated, the presented findings may open the door for DED-relevant experimentation on porcine and murine model systems.
CRIS-Team Scopus Importer:2022-07-01
Keywords: Dry eye disease; Dry eye syndrome; Lacrimal apparatus; Lacrimal functional unit; Meibomian gland dysfunction; Ocular surface; Tear film; Urea transporter